Evaluation of a Seven-Week Web-Based Happiness Training to Improve Psychological Well-Being, Reduce Stress, and Enhance Mindfulness and Flourishing: A Randomized Controlled Occupational Health Study. (31st December 2013) - Feicht, T.; Wittmann, M.; Jose, G.; Mock, A.; von Hirschhausen, E.; Esch, T.
Abstract : Background . As distress in society increases, including work environments, individual capacities to compete with stress have to be strengthened. Objective . We examined the impact of a web-based happiness training on psychological and physiological parameters, by self-report and objective means, in an occupational health setting. Methods . Randomized controlled trial with 147 employees. Participants were divided into intervention (happiness training) and control groups (waiting list). The intervention consisted of a seven-week online training. Questionnaires were administered before, after, and four weeks after training. The following scales were included: VAS (happiness and satisfaction), WHO-5 Well-being Index, Stress Warning Signals, Freiburg Mindfulness Inventory, Recovery Experience Questionnaire, and Flourishing Scale. Subgroup samples for saliva cortisol and alpha-amylase determinations were taken, indicating stress, and Attention Network Testing for effects on attention regulation. Results . Happiness (P = 0.000 ; d = 0.93 ), satisfaction (P = 0.000 ; d = 1.17 ), and quality of life (P = 0.000 ; d = 1.06 ) improved; perceived stress was reduced (P = 0.003 ; d = 0.64 ); mindfulness (P = 0.006 ; d = 0.62 ), flourishing (P = 0.002 ; d = 0.63 ), and recovery experience (P = 0.030 ; d = 0.42 ) also increased significantly. No significant differences in the Attention Network Tests and saliva results occurred (intergroup), except for one saliva value. Conclusions . The web-based training can be a useful tool for stabilizing health/psychological well-being and work/life balance.